The compressive behaviour of natural and recycled aggregate concrete during and after exposure to elevated temperatures. (June 2021) - Pliya, P.; Hajiloo, H.; Romagnosi, S.; Cree, D.; Sarhat, S.; Green, M.F.
Abstract: Applications of recycled concrete aggregate (RCA) in the production of new concrete can help in addressing the growing solid waste challenge and preserving natural aggregate resources from depletion. The behaviour of RCA concrete under different loading scenarios is a well-studied topic at both material and structural levels. However, little attention has been directed at studying the performance of concrete made with RCA at elevated temperatures. Most of the previous studies have focused on the residual mechanical response of coarse RCA concrete after exposure to elevated temperatures. This paper presents an experimental study on the behaviour of natural aggregate concrete (NAC) and recycled aggregate concrete (RAC) during and after exposure to elevated temperatures. The RAC in this study contained both coarse and fine recycled concrete aggregates (CRCA and FRCA) as partial replacements of natural aggregates. The compressive strength of the NAC and RAC were evaluated at ambient temperature (unheated), after exposure to three different temperatures of 150, 300, and 450 °C (residual), at an elevated temperature of 450 °C without preloading (steady state), and during heating while being preloaded with 40% and 70% of the ambient strength (transient). A rate of 2 °C/min was used in all these heating scenarios. The results indicated that concrete with aggregates partially replaced with CRCA and FRCA exhibited good performance at elevated temperatures, and it can be considered comparable to conventional concrete. The results also showed that the compressive strengths measured during elevated temperatures, with or without preloading, were relatively higher than the residual compressive strengths for both RAC and NAC. The total thermal strains were also investigated with Digital Image Correlation. Preloading had an impact on the evolution of the total thermal strains and the occurrence of spalling for the types of concrete that were tested. Highlights: The mechanical properties of RAC were studied at the room, high temperatures, and after heat exposure (residual). The RAC with 30% recycled aggregate exhibits adequate performance at high temperatures to its reference NAC. Specimens preloaded with 70% spalled at a surface temperature of 150 and 450 °C for RAC and NAC, respectively. The preloading at 40% did not seem to have a significant effect on RAC (+1%) compared to that of NAC (−6%).